2015
DOI: 10.1210/jc.2014-4551
|View full text |Cite
|
Sign up to set email alerts
|

A Reverse J-Shaped Association Between Serum 25-Hydroxyvitamin D and Cardiovascular Disease Mortality: The CopD Study

Abstract: In this large observational study, low and high levels of 25(OH)D were associated with cardiovascular disease, stroke, and acute myocardial mortality in a nonlinear, reverse J-shaped manner, with the highest risk at lower levels. Whether this was a causal or associational finding cannot be determined from our data. There is a need for randomized clinical trials that include information on the effects of 25(OH)D levels greater than 100 nmol/L.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
97
4
6

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(110 citation statements)
references
References 39 publications
3
97
4
6
Order By: Relevance
“…Extension of these studies to 52 weeks of ERC treatment [14] demonstrated no increased risks related to these parameters. One observational study has suggested a J-shaped association between serum 25-hydroxyvitamin D levels and all-cause mortality [39], while another study has shown an increased hazard ratio only at low levels of serum 25-hydroyvitamin D [40]. In the present studies, a positive correlation was observed between serum total 25-hydroxyvitamin D and 1,25-dihydroxyvitamin D, but no correlation was observed between serum total 25-hydroxyvitamin D and serum calcium or phosphorus.…”
Section: Discussion/conclusioncontrasting
confidence: 51%
“…Extension of these studies to 52 weeks of ERC treatment [14] demonstrated no increased risks related to these parameters. One observational study has suggested a J-shaped association between serum 25-hydroxyvitamin D levels and all-cause mortality [39], while another study has shown an increased hazard ratio only at low levels of serum 25-hydroyvitamin D [40]. In the present studies, a positive correlation was observed between serum total 25-hydroxyvitamin D and 1,25-dihydroxyvitamin D, but no correlation was observed between serum total 25-hydroxyvitamin D and serum calcium or phosphorus.…”
Section: Discussion/conclusioncontrasting
confidence: 51%
“…Vitamin D deficiency has also been implicated in bone abnormalities in various diseases including infections, diseases cardiovasculares 27-29, endothelial dysfunction 30, some types of neoplasms 31, insulin resistance 32,33, diabetic nephropathy 34, autoimmune diseases, depressives states 35 and decrease in mass muscular 36. Was also associated with high cardiovascular and all causes mortality 37,38.…”
Section: Discussionmentioning
confidence: 99%
“…We found the mutagenesis of key bass pairs in heterodimeric or coactivator binding sites in VDR gene leads to a significant impairment of liganded VDR functions [6,7]. With changed lifestyles in the modern society, people have a low amount of sunlight exposure resulting in reduced vitamin D synthesis in the skin, which largely contributes to current high prevalence of vitamin D deficiency [8,9] that is associated with increased cardiovascular disease mortality among adults, especially with EH [10][11][12].…”
Section: Is Vitamin D Deficiency Causally Linked To Eh?mentioning
confidence: 98%